272PMelatonin increases the chemosensitivity of diffuse large Bell lymphoma cells to Epirubicin by inhibiting P-glycoprotein expression via the NF-κB pathway. (24th November 2019) - Sun, X
Abstract: Background: Epirubicin (EPI) is a first-line chemotherapeutic drug for the clinical treatment of diffuse large B cell lymphoma (DLBCL), but the overexpression of multidrug resistance (MDR) transporter proteins, such as P-glycoprotein (P-gp), renders EPI ineffective. On the basis of some studies, melatonin (MLT) is considered to possess the potential for chemotherapeutic synergy that can be leveraged to overcome MDR. Methods: The human DLBCL cells SUDHL-6 and SUDHL-10 were incubated with MLT and/or EPI for 48 h. Using CCK8 assay, the cell viability of SUDHL-10 and SUDHL-6 cell lines under different treatments were tested. Using AO/EB assay, the apoptosis of SUDHL-6 cell line was detected. Cytochrome c release experiment was used to reveal the further molecular mechanism. Immunofluorescence experiment was used to detect the expression of P-gp of DLBCL cell lines under different drug treatment groups. Rhodamine-123 and epirubicin accumulation test were used to detect the function of P-gp. Immunohistochemical staining studies in tumor tissue of DLBCL disclosed that the expression of P-gp and P65. Western blotting assay and pulldown assay were used to detect the relationship between NF-κB pathway and P-gp exression. Results: Melatonin potentiated the epirubicin-mediated inhibition of cell proliferation and increased epirubicin-induced apoptosis. Melatonin inhibits epirubicin-induced P-glycoprotein expression and the activity of the P-glycoprotein pump.Epirubicin promotes the expression of P-gp by activating the NF-κB pathway. However, melatonin inhibited the epirubicin-mediated activation of NF-κB signaling and the expression of P-gp. Conclusions: Our results demonstrated that MLT inactivating the NF-κB pathway and down-regulating the expression of P-gp, ultimately sensitized EPI-mediated growth suppression of DLBCL cells. Legal entity responsible for the study: The second hospital of Dalian medical university. Funding: Has not received any funding. Disclosure: The author has declared no conflicts of interest.